(untitled) (The Journal of Plant Protection Sciences, 2023)
Five gerbera cultivars were screened for their reaction against spider mite, Tetranychus urticae Koch under the polyhouse conditions. Results showed that the gerbera cultivar Cherany was highly tolerant with lowest mite popu lation (1.62mites/plant) whereas Venezia and Fana were tolerant to spider mite with 7.72 and 9.67 mites per plant, respectively. The gerbera cultivar C. F. Gold (13.31 mites/plant) and Stanza (15.56 mites/plant) were medium tol erant under polyhouse conditions. On the basis of biomorphological characters cultivar stanza has maximum mite population having green coloured leaves and red coloured flowers, while the highly tolerant cultivar Cherany with dark green leaves and pink coloured flower.